Process intensification for sustainable energy conversion - Gallucci, Fausto; Sint Annaland, Martin van (Wiley, 2015)
This book addresses the application of process intensification to sustainable energy production, combining two very topical subject areas. Due to the increasing process of petroleum, sustainable energy production technologies must be developed, for example bioenergy, blue energy, chemical looping combustion, concepts for CO2 capture etc. Process intensification offers significant competitive advantages, because it provides more efficient processes, leading to outstanding cost reduction, increased productivity and more environment-friendly processes.